O-031 Importance of blood flow to human implantation. (6th August 2021) - Pierzynski, P
Abstract text: The success of embryo implantation depends on a plethora of factors, with embryo quality and endometrial receptivity belonging to the most important ones. The receptive phenotype of endometrium develops in reaction to appropriate estrogen stimulation in the proliferative phase and embryo-synchronized maturation warranted by the action of progesterone. Uterine blood supply, myometrial contractions and the activity of local immune cells also belong to important factors affecting the outcome of both natural and assisted reproduction. Endometrial perfusion was shown to be an independent receptivity parameter, showing a direct association with pregnancy outcomes. Historically, the use of Doppler parameters of uterine vessels was studied as a reflection of blood flow to the endometrium. Although some authors showed a correlation between blood flow in uterine arteries and success rates in IVF cycles, it might not reflect the actual endometrial flow as most of the blood volume goes through myometrium, not endometrium. Currently, using available ultrasound tools – 2D/3D Power Doppler with VOCAL (Virtual Organ Computer-Aided Analysis) software enables clinicians to evaluate parameters of endometrial perfusion in a matter of minutes. In this method, ultrasound system can calculate indices reflecting endometrial blood flow - vascularity index (VI), endometrial flow index (FI), and endometrial vascularity flow index (VFI) which are based on the total and relative amounts of Power Doppler signal (corresponding to the blood flow) within the volume of interest. Endometrial blood flow parameters can be altered in implantation limiting conditions such as endometriosis or chronic intrauterine inflammation. It was also shown to be influenced by implantation-related hormones such as oxytocin. Oxytocin receptor antagonists were shown to decrease uterine contractions in non-pregnant uteri of women being prepared for embryo transfer procedure. This class of medications has been extensively studied as potential candidates for medications promoting embryo implantation in IVF-ET treatments. In several studies, it was shown that mixed oxytocin/vasopressin V1A receptor antagonist atosiban, which is currently registered in Europe for the tocolysis in preterm labour, had the potential of improving implantation rates. Interestingly, this effect was confirmed also in women without pronounced contractions. Additionally, it has been demonstrated that oxytocin antagonism enhances endometrial decidualization and influences other parameters necessary for the acquisition of the endometrial receptivity phenotype. Considering that atosiban and other oxytocin antagonists relax uterine blood vessels and increase endometrial blood flow, it was hypothesized that improvement in endometrial perfusion could be an additional mechanism for observed support of embryo implantation. A similar finding was confirmed in our study on nolasiban – a non-peptide, orally active, oxytocin receptor-specific antagonist. In the 1st phase study on volunteers undergoing estrogen/progesterone endometrial preparation reflecting the synchronization for embryo transfer, it was confirmed that application of nolasiban decreased uterine contractions and improved FI and VFI parameters of endometrial perfusion. Such an effect lasted for more than 24 hours after dosing. The study results suggested that oxytocin antagonism could have an effect on endometrial perfusion, and its potential clinical significance requires further investigation. In a longer perspective, once confirmed it would mean that, apart from the possibility of observation of endometrial blood flow, we could have a tool for improving it, which would hopefully lead to improved outcomes of assisted reproduction treatments.